The psychology of social dilemmas: A review - Van Lange, Paul A.M.; Joireman, Jeff; Parks, Craig D.; Van Dijk, Eric (Organizational behavior and human decision processes, 2013)
► This article provides a review on the psychology of social dilemmas, the central topic of this special issue. ► This article provides a careful treatment of the definition of social dilemmas, theories, and recent developments. ► This article introduces relatively unfamiliar readers to the growing field of social dilemmas. Broadly defined, social dilemmas involve a conflict between immediate self-interest and longer-term collective interests. These are challenging situations because acting in one’s immediate self-interest is tempting to everyone involved, even though everybody benefits from acting in the longer-term collective interest. As such, greater knowledge of social dilemmas should help us understand not only the theoretical puzzles of why people cooperate (or not) but also the ways in which cooperation in groups and organizations can be maintained or promoted. This article reviews different types of social dilemmas, highlights recent developments in the field (especially within psychology), and suggests some new avenues for future research. We illustrate that the field of social dilemma is growing and flourishing in terms of theory, interdisciplinary collaboration, and applicability, producing insights that are novel, replicable, and applicable to many social situations where short-term self-interest is at odds with the long-term interests of teams, organizations, or nations.